Obesity‐related health status is a better predictor of pregnancy with fertility treatment than body mass index: a prospective study. Issue 4 (31st May 2016) - Paterson, N.; Sharma, A. M.; Maxwell, C.; Greenblatt, E. M.
Summary: This study assessed whether an obesity‐related health status instrument (Edmonton obesity scoring system – EOSS) or body mass index (BMI) better predicted pregnancy rates in overweight women undergoing fertility treatments. A prospective cohort study was conducted on patients with a BMI ≥ 25 kg m −2 undergoing a fertility treatment cycle (ovulation induction, superovulation, or in vitro fertilization). Obesity‐related health status including blood pressure, blood work, health history, and functional assessment were assessed. A total of 101 patients were included in the study with an average age of 36.3 ± 4.2 years and a mean BMI of 31.8 ± 5.2 kg m −2 . EOSS was found to be statistically predictive of pregnancy rate/cycle (OR 0.51, 95% CI 0.27–0.94; P = 0.03), whereas BMI was not (OR 0.95, 95% CI 0.86–1.05). A similar trend was seen for clinical pregnancy rate/cycle started. However, the association between clinical pregnancy rates and EOSS or BMI did not reach statistical significance (OR 0.53, P = 0.06 and OR 0.98, P = 0.62 respectively). Our results demonstrated that EOSS better predicted pregnancy rates after fertility treatments than BMI. In fact, for every EOSS stage increased by one unit, the odds of pregnancy were approximately halved. A multi‐centre study powered for live birth is warranted to establish effective pre‐fertility management of overweight women.